Characterization of LiMn0.9Fe0.1PO4 as a cathode material for solid-state lithium batteries: A study on its structural and electrical attributes - Zahraa M. Jaafar; hamir Abdul-Jabbar Jumah; Natheer B. Mahmood (Modern Electronic Materials)
This study presents the synthesis of LiMn0.9Fe0.1PO4 (LM9F) and its carbon-coated counterpart, LiMn0.9Fe0.1PO4 with 10% carbon (LM9F-10%C), through a straightforward solid-state method. The synthesis utilized lithium carbonate, manganese (II) acetate tetrahydrate, iron phosphate, ammonium dihydrogen phosphate, and glucose powder as the carbon source. To achieve a fine powder, a high-energy ball milling was performed at 270 rpm for 8 h, followed by calcination at 700 °C for 3 h and sintering at the same temperature for an additional 2 h, under a nitrogen atmosphere to prevent iron oxidation. Thermoanalytical techniques (TGA–DTA–DSC) were applied between 30 °C and 1000 °C to study the thermal decomposition behaviors of the precursors and pinpoint the phase formation temperature, which was identified at 416 °C. X-ray diffraction analysis verified the formation of a pure olivine orthorhombic structure, corroborated by Rietveld refinement. The morphology of the calcined powders, characterized by field emission scanning electron microscopy, showed agglomerated semi-spherical particles with an average size of 34 nm. Fourier transform infrared spectroscopy confirmed the presence of the phosphate groups integral to the olivine framework. Electrical properties measured via an LCR meter across 20 Hz to 100 kHz demonstrated that the inclusion of carbon significantly reduced impedance and improved the electrical performance of the materials.